2005
DOI: 10.1143/jjap.44.7863
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Ion Drift into Underlying Oxides by RF Bias during High-Density Plasma Chemical Vapor Deposition

Abstract: Starting from the non-relativistic field theory of spin-1 2 fermions interacting through the Abelian Chern-Simons term, we show that the quantized field theory leads, in the two-particle sector, to a two-particle Aharonov-Bohm-like Schrödinger equation with an antisymmetric (fermionic) wavefunction and without a delta function term. Calculating perturbatively the field-theoretic two-particle scattering amplitude up to one-loop order, we show that, in contrast to the scalar theory, the contribution of all the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This result is similar to that of the endurance resistance. These results indicate that hydrogen in the plasma Si x O y diffuses to the tunnel oxide by high RF bias during the deposition process of HDP-USG 5) and forms electron trap sites by the heat treatment after the gap film formation. To prove this model, we evaluate the hydrogen profile by secondary ion mass spectrometry (SIMS).…”
Section: Reliabilitymentioning
confidence: 86%
“…This result is similar to that of the endurance resistance. These results indicate that hydrogen in the plasma Si x O y diffuses to the tunnel oxide by high RF bias during the deposition process of HDP-USG 5) and forms electron trap sites by the heat treatment after the gap film formation. To prove this model, we evaluate the hydrogen profile by secondary ion mass spectrometry (SIMS).…”
Section: Reliabilitymentioning
confidence: 86%
“…One is hydrogen-ion drift process and the other is ultraviolet (UV) light induced one. The hydrogen-ion drift process is as follows: Hydrogen ions generated by dissociation of SiH 4 are drifted by high electric field at plasma sheath and in p-SiO x N y H z film during HDP-CVD [6]. Then, hydrogen ions gain high momentum energy and internal one such as radical energy, and energies are high enough to break the ESR-inactive bonds in p-SiO x N y H z film.…”
Section: Hydrogen-trapping Mechanism In P-sio X N Y H Z Filmmentioning
confidence: 99%
“…Recently, another hydrogen-related issue has been reported: Hydrogen-ion drift into underlying layers by radio frequency (RF) bias [6], as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of HDP-CVD device, hydrogen ions dissociated from SiH 4 precursor in plasma have kinetic energy so it can easily penetrate into underlayer drifted by electric field to the Si substrate. It was reported that hydrogen ions in plasma penetrate into underlying thermal oxide -even it is about 100nm thick oxide -and they are drifted into the Si substrate by high electric field (4,5). Although TEOS+O 3 USG process also contains hydrogen species in TEOS precursor, the hydrogen atoms or ions have little kinetic energy to penetrate into underlying layers since there is no applied external electric field or RF bias.…”
Section: Introductionmentioning
confidence: 99%